Numerical simulation of residual stress in low temperature colossal carburised layer on austenitic stainless steel. (2018) - Rong, Dongsong; Jiang, Yong; Gong, Jianming; Peng, Yawei
A numerical model is proposed to quantitatively characterise the residual stress evolutions in low temperature colossal carburised layer on austenitic stainless steel. In this model, on the basis of the consideration of concentration and stress dependent carbon diffusivity, prediction of the carbon concentration distribution and growth regularity of carburised layer is performed. The strain rate is discussed taking the compositive effects of residual stress and carbon concentration gradient. Based on the strain compatibility of carburised layer and substrate, the residual stress is calculated. Meanwhile, a low temperature colossal carburisation experiment is carried out on 316L austenitic stainless steel and the carbon concentration and residual stress are measured to verify the validity of the model. The numerical results of carbon concentration and residual stress distributions agree with the experimental data, indicating that the numerical model established in this paper can be used to investigate the process of low temperature colossal carburisation.